PREFERENSI DAN PENGALAMAN TAMU MENGINAP DI HOTEL SYARIAH DI KOTA BANDUNG - Sandra, Tapiuray Alhira; Ervina, Ersy; Maulida, Ratna Gema (JURNAL ILMIAH EDUNOMIKA, 2023)
This study discusses the incompatibility of preferences and guest experiences that are not in accordance with the theory explained by experts. This study uses a descriptive quantitative method using a questionnaire whose measurement uses a Likert scale. This study intends to determine the characteristics of guests, preferences and experiences of guests while staying at Hotel Syariah in the city of Bandung. This study used 152 respondents, namely hotel guests who had stayed at Syariah Hotels in the city of Bandung. Based on the results of the study, it can be seen that the Halal dimension is the most dominant dimension in the preference variable for guests staying at Syariah Hotels in the city of Bandung. This shows that the majority of Guests choose to stay at Syariah Hotels in the city of Bandung based on halal preferences. Meanwhile, the emotional experience dimension is the most dominant dimension in the guest experience variable. This indicates that the majority of guest experiences stay based on emotional experience. Based on the results of the chi-square test, it was found that guest experience has a significant relationship to preference for staying at Syariah Hotels in the city of Bandung.